Faktor-Faktor yang Mempengaruhi Investor Individu dalam Pengambilan Keputusan Investasi Sekuritas di Bursa Efek Indonesia (BEI) - Septyanto, Dihin (Lembaga Penerbitan Unversitas Esa Unggul, 2013)
AbstractThe goal is to examine and obtain empirical evidence about the factors that affect the behavior of investors in securities investment decision in the Indonesia Stock Exchange using the benefits of financial information (information usefulness ). This study uses causality - explanatory . The study subjects were selected existing individual investors in the Indonesia Stock Exchange 135 respondents . This selection is determined to find out the benefits of financial information in investment , sophisticated and rational attitudes about utility maximization in investment decision-making process . Data analysis using Structural Equation Modeling with AMOS program.The analysis showed that the financial statements do not have the benefit of changing the initial confidence of investors to undertake investment decisions. The study shows that the benefits of financial information has no effect on investment intentions. The analysis also showed that subjective norms to positively affect the investment intentions , that is, the higher the power of social influence , the investor 's intention to invest higher. The study results also showed a positive effect of subjective norm on belief revision. The other results showed the revised beliefs positively affect the investment intentions , it indicates investors' perception of financial and non- financial information that is motivated to change the initial beliefs about the repositioning of stock. The findings of this study are investors were unsophisticated and irrational because it does not use the information in the financial statements of the investment decision-making stock .Keywords: fundamental knowledge , belief revision , subjective normÂ